Open access: academic publishing and its implications for knowledge equity in Kenya - Matheka, Duncan Mwangangi (BioMed Central, 2014)
Traditional, subscription-based scientific publishing has its limitations: often, articles are inaccessible to the majority of researchers in low- and middle-income countries (LMICs), where journal subscriptions or one-time access fees are cost-prohibitive. Open access (OA) publishing, in which journals provide online access to articles free of charge, breaks this barrier and allows unrestricted access to scientific and scholarly information to researchers all over the globe. At the same time, one major limitation to OA is a high publishing cost that is placed on authors. Following recent developments to OA publishing policies in the UK and even LMICs, this article highlights the current status and future challenges of OA in Africa. We place particular emphasis on Kenya, where multidisciplinary efforts to improve access have been established. We note that these efforts in Kenya can be further strengthened and potentially replicated in other African countries, with the goal of elevating the visibility of African research and improving access for African researchers to global research, and, ultimately, bring social and economic benefits to the region. We (1) offer recommendations for overcoming the challenges of implementing OA in Africa and (2) call for urgent action by African governments to follow the suit of high-income countries like the UK and Australia, mandating OA for publicly-funded research in their region and supporting future research into how OA might bring social and economic benefits to Africa.